Composite material for improving UV resistance of HDPE (high-density polyethylene) and preparation method of composite material

By introducing light stabilizers, silane cross-linking technology and melt blending technology into HDPE, the HDPE material is modified, which solves the problem of insufficient UV resistance and flexibility, and significantly improves the overall performance and service life of the material.

CN119552446AInactive Publication Date: 2025-03-04JIANGSU UNIV OF TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510135315.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

HDPE has poor UV resistance and insufficient flexibility in extreme environments, resulting in photooxidation reactions of materials under long-term ultraviolet irradiation, degraded mechanical properties, embrittlement, discoloration and even rupture, and shortened service life.

Method used

By introducing light stabilizers, silane cross-linking technology and melt blending technology, HDPE materials are modified to improve their UV resistance, mechanical properties, water resistance, flexibility and braidability. Specific methods include chemical grafting to firmly bind the light stabilizer to the HDPE molecular structure, enhancing the mechanical properties and waterproofness of the material through silane cross-linking technology, and improving the flexibility and impact resistance of the material through a melt blending process.

Benefits of technology

It significantly improves HDPE's UV resistance, mechanical properties and water resistance, extends the service life of the material, and enhances its stability and durability in extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552446A_ABST
    Figure CN119552446A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and provides a composite material for improving the UV resistance of HDPE and a preparation method of the composite material. Firstly, the hindered amine light stabilizer is grafted to HDPE, so that the UV aging resistance of the material is effectively improved, and the performance of the material is still kept stable when the material is exposed to the sun for a long time; secondly, vinyl silane is adopted for silane crosslinking, so that the mechanical property and water resistance of HDPE are enhanced, and the material is endowed with higher structural strength and weather resistance; finally, a proper amount of elastomer and plasticizer are added in the melting and mixing process, so that the material has better flexibility and processability while maintaining the strength. The modified HDPE material is suitable for various application fields requiring ultraviolet irradiation resistance, mechanical stress resistance and flexible processing characteristics. The anti-ultraviolet HDPE material is outstanding in anti-ultraviolet effect, mechanical property improvement and flexibility improvement, the service life of the HDPE material is remarkably prolonged, and the application range of the HDPE material is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials and relates to a composite material for improving the anti-UV performance of HDPE and a preparation method thereof. Background Art

[0002] High-density polyethylene (HDPE) is a common thermoplastic polymer that has been widely used in industry and daily life due to its many excellent properties. First of all, HDPE has excellent mechanical properties, especially high tensile strength and excellent wear resistance, making it an ideal choice for manufacturing high-strength products such as pipes, containers, automotive parts and building materials. Secondly, HDPE's chemical corrosion resistance is also very outstanding. It can resist the erosion of a variety of acids, alkalis, salts and organic solvents, so it is widely used in chemical storage tanks, pipelines and packaging materials. In addition, HDPE's processing performance is also quite good. Its low melting point and high processing fluidity make it show high efficiency in injection molding, extrusion, blow molding and other processes.

[0003] However, despite the above advantages of HDPE, it has also exposed some limitations in practical applications, especially in some extreme environments. First, HDPE's UV resistance is relatively poor. After long-term exposure to ultraviolet radiation in sunlight, HDPE is prone to photooxidation, resulting in the breakage of its molecular structure and the decline of mechanical properties, which ultimately causes the material to become brittle, discolored, or even cracked, shortening its service life. Secondly, HDPE itself is not flexible enough. Although it has high tensile strength, its ductility and impact resistance are weak, which makes it perform poorly in applications requiring high flexibility and impact resistance. Announcement No. CN108864528A discloses a UV-resistant polyethylene material for water horses, which uses high-density polyethylene, carbon black, modified titanium dioxide, maleic anhydride grafted polyolefin and other substances to prepare UV-resistant polyethylene materials, but the calcination steps designed in its preparation process increase the complexity of processing and increase production costs. Due to these defects, HDPE cannot meet the high performance requirements of the product. In response to these problems, HDPE needs to be further modified to develop composite materials that can effectively resist UV and have good mechanical properties to achieve a wider range of applications. Summary of the invention

[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a composite material and a preparation method thereof for improving the UV resistance of HDPE. The present invention aims to modify the HDPE material by introducing a light stabilizer, silane crosslinking technology and melt blending technology to improve its comprehensive properties such as UV resistance, mechanical properties, water resistance, flexibility and weavability. The light stabilizer is firmly combined in the HDPE molecular structure by chemical grafting, and the HDPE is chemically modified by silane crosslinking technology to enhance the mechanical properties and water resistance of the material. Through the melt blending process, the elastomer is uniformly dispersed in the HDPE matrix to form a composite structure, thereby improving the flexibility, ductility and impact resistance of the material. In addition, by adding a small amount of plasticizer, the inter-molecular chain force of HDPE is further reduced, the processing fluidity and plasticity of the material are improved, and its easy processing in fiber manufacturing and weaving applications is ensured, thereby meeting the needs of actual production.

[0005] To achieve this object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a method for preparing a composite material for improving the UV resistance of HDPE, the preparation method comprising: Step S1, placing HDPE particles in a vacuum drying oven and drying at a first temperature; dissolving a hindered amine light stabilizer in a reaction solvent to prepare a mixed solution A, mixing the dried HDPE with the mixed solution A, adding an initiator, setting a reflux condenser, and heating to a second temperature under the protection of an inert gas for reaction, and stirring at a first stirring speed, cooling to room temperature after the reaction is completed, and washing the product with a reaction solvent, placing the washed product in a vacuum dryer, and drying at a third temperature to obtain a product A; Step S2, adding a silane coupling agent to a reaction solvent, and adding a catalyst, stirring at a second stirring speed to make the solution uniform, then adding deionized water for hydrolysis reaction, and stirring at a third stirring speed under the protection of an inert gas to obtain a mixed solution B, mixing the product A with the mixed solution B, reacting at a fourth temperature and at a first stirring speed under the protection of an inert gas, cooling to room temperature after the reaction is completed, and washing the product with a reaction solvent, placing the washed product in a vacuum dryer, and drying at a third temperature to obtain a product B; Step S3, adding product B at the second temperature, adding elastomer, plasticizer, lubricant and antioxidant in sequence after product B is melted, mixing evenly at the fourth stirring speed, and then cooling and granulating to obtain a composite material with improved anti-UV performance of HDPE.

[0006] Although HDPE has many excellent properties, some of its defects in practical applications are due to its molecular structure and polymer properties: (1) HDPE has poor UV resistance, which is mainly attributed to its non-polar long-chain molecular structure. The energy of ultraviolet light is enough to break the CH and CC bonds in HDPE, especially the short-wavelength UV-B light band. The energy of this wavelength is high, which can easily cause the polyethylene molecular chain to break. After HDPE is irradiated with UV, the free radicals generated can easily trigger a chain reaction, leading to further degradation of the material. Oxygen and free radicals react to form peroxides, which accelerate the oxidative degradation of the polymer. The above reactions lead to a decrease in the molecular weight of HDPE and a decrease in the mechanical properties of the polymer, which manifests as embrittlement, discoloration, cracking and other problems of the material. (2) Insufficient flexibility. HDPE is a polymer with a high degree of crystallinity. Its molecular chains form regular crystal regions when solidified. These crystal regions give the material high rigidity and strength, but limit the activity of the molecular chains, thereby reducing the ductility and flexibility of the material. In a low-temperature environment, the activity of the HDPE molecular chains is further restricted, and the influence of the crystal region is more obvious, causing the material to become more fragile and prone to breakage and damage.

[0007] The function of HDPE grafted hindered amine light stabilizer is: (1) Under long-term exposure to ultraviolet rays, the chemical bonds in HDPE molecules (especially CH bonds) easily absorb energy and break, generating free radicals. Ultraviolet rays, especially the energy in the UV-B band (280-320nm), can break the CH bonds in HDPE molecules, generating polymer free radicals and hydrogen free radicals. These free radicals react with oxygen to generate peroxide free radicals, which further react with HDPE molecules to generate more free radicals, resulting in molecular chain breakage. Hindered amine light stabilizers are a class of compounds containing hindered amine structures. They capture and neutralize free radicals in polymers through a unique mechanism, inhibiting the photo-oxidative degradation process. Hindered amine light stabilizers can quickly react with polymer free radicals or peroxide free radicals through the action of hindered amine groups to generate stable nitrogen oxides. Hindered amine groups react with free radicals to generate N-amine oxides. This product has high stability and can continue to work to capture new free radicals, effectively terminating the chain reaction of photo-oxidative degradation and preventing further breakage of polyethylene molecular chains. (2) Compared with directly adding the hindered amine light stabilizer to the HDPE matrix, chemically bonding the hindered amine light stabilizer to the HDPE molecular chain by grafting avoids the migration, volatilization or loss of the light stabilizer during long-term use when conventional physical addition is used. Through chemical grafting, the hindered amine light stabilizer molecules become part of the HDPE molecules and are not easy to migrate or be extracted, so that the light stabilizer can play a role in the material for a long time, improving the durability of its UV resistance. In addition, the distribution of the hindered amine light stabilizer in the HDPE matrix is ​​more uniform. The grafting reaction ensures that the light stabilizer can be evenly distributed throughout the material, ensuring the consistency of the UV resistance of various parts of the material, thereby greatly improving the long-term stability of the material.

[0008] The role of adding silane crosslinking agent: (1) Silane crosslinking improves the tensile strength and impact resistance of the material by forming stable crosslinking points between HDPE molecular chains. During the silane crosslinking process, vinyl triethoxysilane first reacts with active points (such as free radical sites) on the HDPE molecular chain through a free radical initiation reaction to form a C-Si covalent bond, allowing vinyl triethoxysilane to be successfully grafted onto the HDPE molecule. The ethoxy group (-OC2H5) of vinyl triethoxysilane is hydrolyzed to form a silanol group (Si-OH), which is then converted into a Si-O-Si bond through a condensation reaction. The three-dimensional network structure formed by these Si-O-Si bonds provides crosslinking points between molecules, thereby improving the mechanical properties of the material. (2) Silane crosslinking makes HDPE more water-resistant and the surface of the material becomes more hydrophobic. During the silane crosslinking process, the silane groups grafted on HDPE form Si-O-Si bonds through hydrolysis and polycondensation reactions. The Si-O-Si bonds not only have a tight structure but also have excellent hydrophobicity, which reduces the hydrophilicity of the material surface. It is difficult for water molecules to penetrate the cross-linked siloxane network, thereby greatly improving the waterproof performance of the material. (3) After cross-linking, HDPE has enhanced resistance to various chemicals and is not easily susceptible to chemical erosion or degradation. In particular, it can maintain good stability and durability in corrosive environments. The Si-O-Si bonds generated by the cross-linking reaction are highly chemically inert and are not easily attacked by acids, alkalis or organic solvents. The Si-O-Si bonds have high bond energy and excellent chemical stability, which can effectively prevent chemicals from reacting with the HDPE molecular chain.

[0009] As a preferred technical solution of the present invention, in step S1, the mass of the HDPE is 20-30g, for example, it can be 20g, 21g, 22g, 23g, 24g, 25g, 26g, 27g, 28g, 29g or 30g, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0010] In some optional instances, the first temperature is 60-70°C, for example, it can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0011] In some optional examples, the drying time at the first temperature is 4-6 hours, for example, it can be 4.0h, 4.2h, 4.4h, 4.6h, 4.8h, 5.0h, 5.2h, 5.4h, 5.6h, 5.8h or 6.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0012] In some optional instances, the mass fraction of the mixed solution is 0.5-2.0wt.%, for example, it can be 0.5wt.%, 0.6wt.%, 0.7wt.%, 0.8wt.%, 0.9wt.%, 1.0wt.%, 1.1wt.%, 1.2wt.%, 1.3wt.%, 1.4wt.%, 1.5wt.%, 1.6wt.%, 1.7wt.%, 1.8wt.%, 1.9wt.% or 2.0wt.%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0013] In some optional examples, the mass of the initiator is 0.5-1.0wt.% of the mass of HDPE, for example, it can be 0.5wt.%, 0.55wt.%, 0.60wt.%, 0.65wt.%, 0.70wt.%, 0.75wt.%, 0.80wt.%, 0.85wt.%, 0.90wt.%, 0.95wt.% or 1.0wt.%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0014] In some optional examples, the flow rate of the nitrogen gas is 4-6 mL / min, for example, it can be 4.0 mL / min, 4.2 mL / min, 4.4 mL / min, 4.6 mL / min, 4.8 mL / min, 5.0 mL / min, 5.2 mL / min, 5.4 mL / min, 5.6 mL / min or 6.0 mL / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0015] In some optional instances, the second temperature is 180-200°C, for example, it can be 180°C, 182°C, 184°C, 186°C, 188°C, 190°C, 192°C, 194°C, 196°C, 198°C or 200°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0016] In some optional examples, the reaction time is 2-3h, for example, it can be 2.0h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h or 3.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0017] In some optional instances, the third temperature is 55-65°C, for example, it can be 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C or 65°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] In some optional examples, the drying time at the third temperature is 6-8h, for example, it can be 6.0h, 6.2h, 6.4h, 6.6h, 6.8h, 7.0h, 7.2h, 7.4h, 7.6h, 7.8h or 8.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] As a preferred technical solution of the present invention, in step S2, the mass of the silane coupling agent is 1-2% of the mass of the product A, for example, it can be 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2.0%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0020] In some optional examples, the volume of the reaction solvent is 150-200 mL, for example, it can be 150 mL, 155 mL, 160 mL, 165 mL, 170 mL, 175 mL, 180 mL, 185 mL, 190 mL, 195 mL or 200 mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0021] In some optional examples, the mass of the catalyst is 0.5-2.0wt.% of the mass of product A, for example, it can be 0.5wt.%, 0.6wt.%, 0.7wt.%, 0.8wt.%, 0.9wt.%, 1.0wt.%, 1.1wt.%, 1.2wt.%, 1.3wt.%, 1.4wt.%, 1.5wt.%, 1.6wt.%, 1.7wt.%, 1.8wt.%, 1.9wt.% or 2.0wt.%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] In some optional instances, the mass of the deionized water is 2-5 g, for example, 2.0 g, 2.3 g, 2.6 g, 2.9 g, 3.2 g, 3.5 g, 3.8 g, 4.1 g, 4.4 g, 4.7 g or 5.0 g, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0023] In some optional examples, the flow rate of the nitrogen gas is 4-6 mL / min, for example, it can be 4.0 mL / min, 4.2 mL / min, 4.4 mL / min, 4.6 mL / min, 4.8 mL / min, 5.0 mL / min, 5.2 mL / min, 5.4 mL / min, 5.6 mL / min or 6.0 mL / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] In some optional examples, the mass of the product A is 20-30g, for example, it can be 20g, 21g, 22g, 23g, 24g, 25g, 26g, 27g, 28g, 29g or 30g, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] In some optional instances, the fourth temperature is 150-180°C, for example, it can be 150°C, 153°C, 156°C, 159°C, 162°C, 165°C, 168°C, 171°C, 174°C, 177°C or 180°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] In some optional examples, the flow rate of the nitrogen gas is 4-6 mL / min, for example, it can be 4.0 mL / min, 4.2 mL / min, 4.4 mL / min, 4.6 mL / min, 4.8 mL / min, 5.0 mL / min, 5.2 mL / min, 5.4 mL / min, 5.6 mL / min or 6.0 mL / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] In some optional examples, the reaction time is 1-2h, for example, it can be 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0028] In some optional instances, the third temperature is 55-65°C, for example, it can be 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C or 65°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] In some optional examples, the drying time is 6-8h, for example, it can be 6.0h, 6.2h, 6.4h, 6.6h, 6.8h, 7.0h, 7.2h, 7.4h, 7.6h, 7.8h or 8.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] As a preferred technical solution of the present invention, in step S3, the second temperature is 180-200°C, for example, it can be 180°C, 182°C, 184°C, 186°C, 188°C, 190°C, 192°C, 194°C, 196°C, 198°C or 200°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] In some optional examples, the mass of the product B is 30-40g, for example, it can be 30g, 31g, 32g, 33g, 34g, 35g, 36g, 37g, 38g, 39g or 40g, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] In some optional instances, the mass of the elastomer is 3-5g, for example, it may be 3.0g, 3.2g, 3.4g, 3.6g, 3.8g, 4.0g, 4.2g, 4.4g, 4.6g, 4.8g or 5.0g, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] In some optional examples, the mass of the plasticizer is 1-2g, for example, it can be 1.0g, 1.1g, 1.2g, 1.3g, 1.4g, 1.5g, 1.6g, 1.7g, 1.8g, 1.9g or 2.0g, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] In some optional instances, the mass of the lubricant is 1-2g, for example, it can be 1.0g, 1.1g, 1.2g, 1.3g, 1.4g, 1.5g, 1.6g, 1.7g, 1.8g, 1.9g or 2.0g, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] In some optional examples, the mass of the antioxidant is 2-3g, for example, it can be 2.0g, 2.1g, 2.2g, 2.3g, 2.4g, 2.5g, 2.6g, 2.7g, 2.8g, 2.9g or 3.0g, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] In a second aspect, the present invention provides a composite material for improving the UV resistance of HDPE.

[0037] Compared with the prior art, the present invention has the following beneficial effects: (1) By grafting hindered amine light stabilizers on the HDPE molecular chain, the UV resistance of the composite material has been improved, which can effectively prevent photo-oxidative degradation caused by ultraviolet rays. Hindered amine light stabilizers capture free radicals generated under ultraviolet irradiation and inhibit free radical chain reactions, thereby effectively preventing the breakage and degradation of polymer molecular chains. In addition, the N-amine oxide generated by the hindered amine light stabilizer can be regenerated into a hindered amine structure in the redox cycle, and can still maintain effective light stabilization function under long-term ultraviolet radiation. Through this "self-repairing" mechanism, the light stabilizer can play a role for a long time, greatly extending the service life of HDPE; (2) Through silane crosslinking, the mechanical properties of HDPE materials are enhanced. During the silane crosslinking process, vinyl triethoxysilane forms a Si-O-Si three-dimensional network structure between the molecular chains of HDPE through hydrolysis and polycondensation. This crosslinking structure increases the interaction between the molecular chains of the material, reduces the movement of the molecular chains, and makes the material less likely to deform or break when subjected to external forces; (3) The flexibility of HDPE materials is significantly improved by the combined use of elastomer blending and plasticizers. The addition of elastomers can form a multiphase structure with the HDPE matrix, in which the elastomer part can absorb and disperse external forces when the material is subjected to stress, reduce stress concentration, and thus improve the impact resistance and flexibility of the material. Plasticizers reduce the cohesive energy between HDPE molecular chains, making the molecular chains more likely to slide, thereby improving the ductility and softness of the material. This combined modification enables HDPE materials to have better deformation ability under the action of external forces while ensuring that they do not lose their original mechanical strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 A flow chart of a method for preparing a composite material for improving the anti-UV performance of HDPE provided in Examples 1-8 of the present invention; Figure 2 This is an electron microscope image of a composite material for improving the UV resistance of HDPE prepared in an embodiment of the present invention; Figure 3 This is an electron microscope image of a composite material for improving the UV resistance of HDPE prepared in an embodiment of the present invention; Figure 4 This is an electron microscope image of a composite material for improving the UV resistance of HDPE prepared in an embodiment of the present invention. DETAILED DESCRIPTION

[0039] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.

[0040] The chemical reagents used in the examples and comparative examples of the present invention are all commercially available products, and their brands, specifications and manufacturer information are as follows: HDPE, content ≥99%, Hebei Zaimei Technology Development Co., Ltd.; Tinuvin 770, content ≥98%, Tianjin Lianlong New Materials Co., Ltd.; Dichloromethane, content ≥99%, Jiangsu Runfeng Synthetic Technology Co., Ltd.; Potassium persulfate, content ≥99%, Shanghai Aladdin Biochemical Technology Co., Ltd.; Nitrogen, content ≥99%, Tianjin Fuyu Fine Chemical Co., Ltd.; Vinyl triethoxysilane, content ≥99%, Shandong Fengpan New Materials Co., Ltd.; Dibutyltin dilaurate, content ≥98%, Nantong Haotai Chemical Products Co., Ltd.; Ethylene octene copolymer, content ≥98%, Hangzhou Jieheng Chemical Co., Ltd.; Ethylene-vinyl acetate copolymer, content ≥99%, Wuhan Jiyesheng Chemical Co., Ltd.; Tributyl citrate, content ≥98%, Shanghai MacLean Biochemical Technology Co., Ltd.; Di(2-ethylhexyl) phthalate, content ≥98%, Henan Wokas Biotechnology Co., Ltd.; Zinc stearate, content ≥99%, Zibo Yujin Trading Co., Ltd.; Antioxidant 1010, content ≥98%, Qingdao Zhenguang Functional Materials Technology Co., Ltd.; Antioxidant 168, content ≥98%, Qingdao Zhenguang Functional Materials Technology Co., Ltd.; Other raw materials can be purchased from the market.

[0041] Example 1

[0042] This embodiment provides a method for preparing a composite material with improved UV resistance of HDPE, such as Figure 1 As shown, the preparation method specifically comprises the following steps: Step S1, putting 22g HDPE particles into a vacuum drying oven and drying at 64°C for 5.3h; dissolving 1.5g Tinuvin770 in 100mL dichloromethane to prepare a mixed solution A with a mass fraction of 1.5wt.%, mixing the dried HDPE with solution A, adding 0.14g potassium persulfate, setting a reflux condenser, and heating to 188°C for reaction under nitrogen protection at a flow rate of 4.8mL / min, and stirring at 330rpm for 2.3h. After the reaction is completed, cooling to room temperature, washing the product with dichloromethane, and placing the washed product in a vacuum dryer, drying at 59°C for 6.4h to obtain product A; Step S2, adding 0.25g of vinyltriethoxysilane to 170ml of dichloromethane, and adding 0.04g of dibutyltin dilaurate, stirring at 130rpm for 26min to make the solution uniform, then adding 3.7g of deionized water for hydrolysis reaction, and stirring at 380rpm for 44min under the protection of nitrogen at 4.8mL / min to obtain a mixed solution B, mixing 25g of product A with the mixed solution B, reacting at 330rpm for 1.3h at 162°C and under the protection of nitrogen at a flow rate of 4.8mL / min, cooling to room temperature after the reaction, and washing the product with dichloromethane, placing the washed product in a vacuum dryer, and drying it at 60°C for 6.7h to obtain product B; Step S3, adding 36g of product B at 185°C, and after product B is melted, adding 4.1g of ethylene octene copolymer, 1.1g of tributyl citrate, 1.3g of zinc stearate and 2.2g of antioxidant 1010 in sequence, mixing at a speed of 120rpm for 15min, and then cooling and granulating to obtain a composite material with improved UV resistance of HDPE.

[0043] Figure 2 , Figure 3 and Figure 4 This is an electron microscope image of a composite material prepared in this example for improving the UV resistance of HDPE.

[0044] Example 2

[0045] This embodiment provides a method for preparing a composite material with improved UV resistance of HDPE, such as Figure 1 As shown, the preparation method specifically comprises the following steps: Step S1, putting 28g of HDPE particles into a vacuum drying oven and drying at 61°C for 4.3h; dissolving 1.1g of Tinuvin 770 in 100mL of dichloromethane to prepare a mixed solution A with a mass fraction of 1.1wt.%, mixing the dried HDPE with solution A, adding 0.24g of potassium persulfate, setting a reflux condenser, and heating to 184°C for reaction under nitrogen protection at a flow rate of 5.2mL / min, and stirring at 310rpm for 2.6h. After the reaction is completed, cooling to room temperature, washing the product with dichloromethane, and placing the washed product in a vacuum dryer, drying at 62°C for 7.3h to obtain product A; Step S2, adding 0.37g of vinyltriethoxysilane to 180ml of dichloromethane, and adding 0.03g of dibutyltin dilaurate, stirring at 160rpm for 22min to make the solution uniform, then adding 2.8g of deionized water for hydrolysis reaction, and stirring at 410rpm for 38min under the protection of nitrogen at 5.2mL / min to obtain a mixed solution B, mixing 22g of product A with the mixed solution B, reacting at 310rpm for 1.6h at 175°C and under the protection of nitrogen at a flow rate of 5.2mL / min, cooling to room temperature after the reaction, and washing the product with dichloromethane, placing the washed product in a vacuum dryer, and drying it at 62°C for 7.3h to obtain product B; Step S3, adding 33 g of product B at 192° C., and after product B is melted, adding 3.6 g of ethylene octene copolymer, 1.5 g of di(2-ethylhexyl) phthalate, 1.3 g of zinc stearate and 2.7 g of antioxidant 1010 in sequence, mixing at a speed of 110 rpm for 13 min, and then cooling and granulating to obtain a composite material with improved UV resistance of HDPE.

[0046] Example 3

[0047] This embodiment provides a method for preparing a composite material with improved UV resistance of HDPE, such as Figure 1 As shown, the preparation method specifically comprises the following steps: Step S1, putting 26g of HDPE particles into a vacuum drying oven and drying at 66°C for 5.5h; dissolving 1.7g of Tinuvin 770 in 100mL of dichloromethane to prepare a mixed solution A with a mass fraction of 1.7wt.%, mixing the dried HDPE with solution A, adding 0.16g of potassium persulfate, setting a reflux condenser, and heating to 194°C for reaction under nitrogen protection at a flow rate of 4.5mL / min, and stirring at 350rpm for 2.1h. After the reaction is completed, cooling to room temperature, washing the product with dichloromethane, and placing the washed product in a vacuum dryer, drying at 59°C for 6.6h to obtain product A; Step S2, adding 0.49g of vinyltriethoxysilane to 175ml of dichloromethane, and adding 0.04g of dibutyltin dilaurate, stirring at 140rpm for 27min to make the solution uniform, then adding 2.8g of deionized water for hydrolysis reaction, and stirring at 390rpm for 42min under the protection of nitrogen at 4.5mL / min to obtain a mixed solution B, mixing 27g of product A with the mixed solution B, reacting at 350rpm for 1.3h at 167°C and under the protection of nitrogen at a flow rate of 4.5mL / min, cooling to room temperature after the reaction, and washing the product with dichloromethane, placing the washed product in a vacuum dryer, and drying it at 60°C for 7.7h to obtain product B; Step S3, adding 32g of product B at 186°C, and after product B is melted, adding 4.3g of ethylene octene copolymer, 1.7g of tributyl citrate, 1.4g of zinc stearate and 2.2g of antioxidant 1010 in sequence, mixing at a speed of 120rpm for 18min, and then cooling and granulating to obtain a composite material with improved UV resistance of HDPE.

[0048] Example 4

[0049] This embodiment provides a method for preparing a composite material with improved UV resistance of HDPE, such as Figure 1 As shown, the preparation method specifically comprises the following steps: Step S1, putting 20g of HDPE particles into a vacuum drying oven and drying at 64°C for 5.0h; dissolving 0.9g of Tinuvin770 in 100mL of dichloromethane to prepare a mixed solution A with a mass fraction of 0.9wt.%, mixing the dried HDPE with solution A, adding 0.18g of potassium persulfate, setting a reflux condenser, and heating to 190°C for reaction under nitrogen protection at a flow rate of 4.2mL / min, and stirring at 360rpm for 2.6h. After the reaction is completed, cooling to room temperature, washing the product with dichloromethane, and placing the washed product in a vacuum dryer, drying at 61°C for 7.5h to obtain product A; Step S2, adding 0.41g of vinyltriethoxysilane to 169ml of dichloromethane, and adding 0.03g of dibutyltin dilaurate, stirring at 180rpm for 22min to make the solution uniform, then adding 4.6g of deionized water for hydrolysis reaction, and stirring at 440rpm for 46min under the protection of nitrogen at 4.2mL / min to obtain a mixed solution B, mixing 30g of product A with the mixed solution B, reacting at 370rpm for 1.7h at 157°C and under the protection of nitrogen at a flow rate of 4.2mL / min, cooling to room temperature after the reaction, and washing the product with dichloromethane, placing the washed product in a vacuum dryer, and drying it at 62°C for 6.3h to obtain product B; Step S3, adding 38g of product B at 190°C, and after product B is melted, adding 3.9g of ethylene octene copolymer, 1.1g of di(2-ethylhexyl) phthalate, 1.8g of zinc stearate and 2.7g of antioxidant 1010 in sequence, mixing at a speed of 120rpm for 11min, and then cooling and granulating to obtain a composite material with improved UV resistance of HDPE.

[0050] Example 5

[0051] This embodiment provides a method for preparing a composite material with improved UV resistance of HDPE, such as Figure 1 As shown, the preparation method specifically comprises the following steps: Step S1, putting 24g HDPE particles into a vacuum drying oven and drying at 61°C for 5.5h; dissolving 1.3g Tinuvin770 in 100mL dichloromethane to prepare a mixed solution A with a mass fraction of 1.3wt.%, mixing the dried HDPE with solution A, adding 0.21g potassium persulfate, setting a reflux condenser, and heating to 183°C for reaction under nitrogen protection at a flow rate of 4.9mL / min, and stirring at 350rpm for 2.2h. After the reaction is completed, cooling to room temperature, washing the product with dichloromethane, and placing the washed product in a vacuum dryer, drying at 57°C for 7.8h to obtain product A; Step S2, adding 0.35g of vinyltriethoxysilane to 185ml of dichloromethane, and adding 0.04g of dibutyltin dilaurate, stirring at 140rpm for 26min to make the solution uniform, then adding 3.7g of deionized water for hydrolysis reaction, and stirring at 380rpm for 41min under the protection of nitrogen at 4.9mL / min to obtain a mixed solution B, mixing 28g of product A with the mixed solution B, reacting at 320rpm for 1.4h at 157°C and under the protection of nitrogen at a flow rate of 4.9mL / min, cooling to room temperature after the reaction, and washing the product with dichloromethane, placing the washed product in a vacuum dryer, and drying it at 61°C for 7.4h to obtain product B; Step S3, adding 33g of product B at 186°C, and after product B is melted, adding 4.4g of ethylene octene copolymer, 1.7g of di(2-ethylhexyl) phthalate, 1.4g of zinc stearate and 2.2g of antioxidant 1010 in sequence, mixing at a speed of 130rpm for 16min, and then cooling and granulating to obtain a composite material with improved UV resistance of HDPE.

[0052] Example 6

[0053] This embodiment provides a method for preparing a composite material with improved UV resistance of HDPE, such as Figure 1 As shown, the preparation method specifically comprises the following steps: Step S1, putting 25g of HDPE particles into a vacuum drying oven and drying at 64°C for 5.2h; dissolving 0.8g of Tinuvin770 in 100mL of dichloromethane to prepare a mixed solution A with a mass fraction of 0.8wt.%, mixing the dried HDPE with solution A, adding 0.20g of potassium persulfate, setting a reflux condenser, and heating to 191°C for reaction under nitrogen protection at a flow rate of 4.7mL / min, and stirring at 360rpm for 2.9h. After the reaction is completed, cooling to room temperature, washing the product with dichloromethane, and placing the washed product in a vacuum dryer, drying at 55°C for 7.9h to obtain product A; Step S2, adding 0.38g of vinyltriethoxysilane to 170ml of dichloromethane, and adding 0.02g of dibutyltin dilaurate, stirring at 170rpm for 21min to make the solution uniform, then adding 2.7g of deionized water for hydrolysis reaction, and stirring at 400rpm for 36min under the protection of nitrogen at 4.7mL / min to obtain a mixed solution B, mixing 24g of product A with the mixed solution B, reacting at 380rpm for 1.8h at 166°C and under the protection of nitrogen at a flow rate of 4.7mL / min, cooling to room temperature after the reaction, and washing the product with dichloromethane, placing the washed product in a vacuum dryer, and drying it at 60°C for 7.0h to obtain product B; Step S3, adding 35g of product B at 190°C, and after product B is melted, adding 4.7g of ethylene octene copolymer, 1.4g of tributyl citrate, 1.9g of zinc stearate and 2.2g of antioxidant 1010 in sequence, mixing at a speed of 110rpm for 14min, and then cooling and granulating to obtain a composite material with improved UV resistance of HDPE.

[0054] Example 7

[0055] This embodiment provides a method for preparing a composite material with improved UV resistance of HDPE, such as Figure 1 As shown, the preparation method specifically comprises the following steps: Step S1, putting 23g HDPE particles into a vacuum drying oven and drying at 61°C for 5.3h; dissolving 0.7g Tinuvin770 in 100mL dichloromethane to prepare a mixed solution A with a mass fraction of 0.7wt.%, mixing the dried HDPE with solution A, adding 0.17g potassium persulfate, setting a reflux condenser, and heating to 200°C for reaction under nitrogen protection at a flow rate of 5.6mL / min, and stirring at 370rpm for 2.1h. After the reaction is completed, cooling to room temperature, washing the product with dichloromethane, and placing the washed product in a vacuum dryer, drying at 61°C for 7.4h to obtain product A; Step S2, adding 0.39g of vinyltriethoxysilane to 160ml of dichloromethane, and adding 0.02g of dibutyltin dilaurate, stirring at 150rpm for 27min to make the solution uniform, then adding 4.6g of deionized water for hydrolysis reaction, and stirring at 390rpm for 44min under the protection of nitrogen at 5.6mL / min to obtain a mixed solution B, mixing 23g of product A with the mixed solution B, reacting at 340rpm for 1.4h at 174°C and under the protection of nitrogen at a flow rate of 5.6mL / min, cooling to room temperature after the reaction, and washing the product with dichloromethane, placing the washed product in a vacuum dryer, and drying it at 58°C for 6.7h to obtain product B; Step S3, adding 32g of product B at 193°C, and after product B is melted, adding 4.1g of ethylene octene copolymer, 1.6g of tributyl citrate, 1.2g of zinc stearate and 2.7g of antioxidant 1010 in sequence, mixing at a speed of 100rpm for 18min, and then cooling and granulating to obtain a composite material with improved UV resistance of HDPE.

[0056] Example 8

[0057] This embodiment provides a method for preparing a composite material with improved UV resistance of HDPE, such as Figure 1 As shown, the preparation method specifically comprises the following steps: Step S1, putting 27g HDPE particles into a vacuum drying oven and drying at 68°C for 5.1h; dissolving 1.5g Tinuvin770 in 100mL dichloromethane to prepare a mixed solution A with a mass fraction of 1.5wt.%, mixing the dried HDPE with solution A, adding 0.16g potassium persulfate, setting a reflux condenser, and heating to 197°C for reaction under nitrogen protection at a flow rate of 5.5mL / min, and stirring at 320rpm for 2.6h. After the reaction is completed, cooling to room temperature, washing the product with dichloromethane, and placing the washed product in a vacuum dryer, drying at 59°C for 6.4h to obtain product A; Step S2, adding 0.41g of vinyltriethoxysilane to 180ml of dichloromethane, and adding 0.03g of dibutyltin dilaurate, stirring at 140rpm for 24min to make the solution uniform, then adding 3.9g of deionized water for hydrolysis reaction, and stirring at 370rpm for 41min under the protection of nitrogen at 5.5mL / min to obtain a mixed solution B, mixing 26g of product A with the mixed solution B, reacting at 380rpm for 1.7h at 162°C and under the protection of nitrogen at a flow rate of 5.5mL / min, cooling to room temperature after the reaction, and washing the product with dichloromethane, placing the washed product in a vacuum dryer, and drying it at 60°C for 7.3h to obtain product B; Step S3, adding 31 g of product B at 187° C., and after product B is melted, adding 3.5 g of ethylene octene copolymer, 1.5 g of di(2-ethylhexyl) phthalate, 1.3 g of zinc stearate and 2.8 g of antioxidant 1010 in sequence, mixing at a speed of 140 rpm for 16 min, and then cooling and granulating to obtain a composite material with improved UV resistance of HDPE.

[0058] Comparative Example 1 This embodiment provides a composite material for improving the UV resistance of HDPE. The difference between this embodiment and embodiment 1 is that the mass of the elastomer ethylene octene copolymer is adjusted to 6.1 g. Compared with embodiment 1, the mass of the elastomer ethylene octene copolymer in this embodiment is increased by 2 g. The increased 2 g is proportionally deducted from product B, tributyl citrate, zinc stearate and antioxidant 1010, so that the mass ratio between the other components except the elastomer ethylene octene copolymer remains unchanged. The other process parameters and operating steps are exactly the same as those in embodiment 1.

[0059] Comparative Example 2 This embodiment provides a composite material for improving the UV resistance of HDPE. The difference between this embodiment and embodiment 1 is that the mass of the elastomer ethylene octene copolymer is adjusted to 2.1 g. Compared with embodiment 1, the mass of the elastomer ethylene octene copolymer in this embodiment is reduced by 2 g, and the reduced 2 g is added to the mass of product B, tributyl citrate, zinc stearate and antioxidant 1010 in equal proportion, so that the mass ratio between the other components except the elastomer ethylene octene copolymer remains unchanged, and the other process parameters and operating steps are exactly the same as those in embodiment 1.

[0060] Comparative Example 3 This embodiment provides a composite material for improving the UV resistance of HDPE. The difference between this embodiment and embodiment 1 is that the mass fraction of the mixed solution A is adjusted to 2.8wt.%, and the mass fraction of the mixed solution A in this embodiment is increased by 1.3wt.% compared with embodiment 1. The increased 1.3wt.% is deducted from the potassium persulfate in a certain proportion. Except that the mass ratios of other components of the mixed solution A remain unchanged, other process parameters and operating steps are exactly the same as those in embodiment 1.

[0061] Comparative Example 4 This embodiment provides a composite material for improving the UV resistance of HDPE. The difference between this embodiment and embodiment 1 is that the mass fraction of the mixed solution A is adjusted to 0.2wt.%, and the mass fraction of the mixed solution A in this embodiment is reduced by 1.3wt.% compared with embodiment 1. The reduced 1.3wt.% is added to potassium persulfate in equal proportion. Except for triethylenetetramine, the mass ratios of other components remain unchanged, and other process parameters and operating steps are exactly the same as those in embodiment 1.

[0062] The anti-UV performance of a composite material for improving the anti-UV performance of HDPE prepared by the present invention is tested according to the national standard GB / T 16422.2-2022; the tensile properties of a composite material for improving the anti-UV performance of HDPE prepared by the present invention are tested according to the national standard GB / T 1040.2-2022; the flexural strength of a composite material for improving the anti-UV performance of HDPE prepared by the present invention is tested according to the national standard GB / T 9341-2008.

[0063] Table 1 Test results of composite materials for improving the anti-UV performance of HDPE in Examples 1-8 and Comparative Examples 1-4

[0064] It can be seen from the test data of Example 1, Comparative Example 1 and Comparative Example 2 that the tensile strength and bending strength of Comparative Example 1 are lower than those of Example 1, the fracture strain rate is higher than that of Example 1, and the mechanical properties of Comparative Example 1 before and after illumination remain basically unchanged; the tensile strength of Comparative Example 2 is higher than that of Example 1, the fracture strain rate is lower than that of Example 1, the bending strength remains basically unchanged, and the mechanical properties of Comparative Example 2 before and after illumination remain basically unchanged. This is because in Comparative Example 1, the amount of elastomer added is too much, the random arrangement and flexible chain segments of the elastomer destroy the crystalline region of HDPE, the force between the molecular chains decreases, resulting in a decrease in the tensile strength and bending strength of the material, and at the same time, the high ductility of the elastomer enables the material to deform more when subjected to force, the sliding and expansion capabilities of the molecular chains are enhanced, and more stress is absorbed to increase the fracture strain rate; in Comparative Example 2, the amount of elastomer added is too little, the crystalline region of HDPE remains intact, and the flexible chain of the elastomer cannot significantly affect the crystallinity, so the tensile strength and bending strength of the material are slightly improved, but the elastomer content is insufficient, the number of flexible chains is small, the deformation capacity of the material when subjected to tension is limited, and the fracture strain rate decreases.

[0065] It can be seen from the test data of Example 1, Comparative Example 1 and Comparative Example 2 that the tensile strength and bending strength of Comparative Example 1 are lower than those of Example 1, the fracture strain rate is higher than that of Example 1, and the mechanical properties of Comparative Example 1 before and after illumination remain basically unchanged; the tensile strength of Comparative Example 2 is higher than that of Example 1, the fracture strain rate is lower than that of Example 1, the bending strength remains basically unchanged, and the mechanical properties of Comparative Example 2 before and after illumination remain basically unchanged. This is because in Comparative Example 1, the amount of elastomer added is too much, the random arrangement and flexible chain segments of the elastomer destroy the crystalline region of HDPE, the force between the molecular chains decreases, resulting in a decrease in the tensile strength and bending strength of the material, and at the same time, the high ductility of the elastomer enables the material to deform more when subjected to force, the sliding and expansion capabilities of the molecular chains are enhanced, and more stress is absorbed to increase the fracture strain rate; in Comparative Example 2, the amount of elastomer added is too little, the crystalline region of HDPE remains intact, and the flexible chain of the elastomer cannot significantly affect the crystallinity, so the tensile strength and bending strength of the material are slightly improved, but the elastomer content is insufficient, the number of flexible chains is small, the deformation capacity of the material when subjected to tension is limited, and the fracture strain rate decreases.

[0066] It can be seen from the test data of Example 1, Comparative Example 3 and Comparative Example 4 that the mechanical properties of the material of Comparative Example 3 are lower than those of Example 1, and the mechanical properties of Comparative Example 3 before and after illumination remain basically unchanged; the mechanical properties of Comparative Example 4 remain basically unchanged from those of Example 1, and the mechanical properties of Comparative Example 4 before and after illumination decrease. This is because there are too many hindered amine light stabilizers in Comparative Example 3, which weakens the inter-polymer chain interaction of the material and may destroy the crystalline structure of the polymer, resulting in a decrease in the overall mechanical properties of the material; in Comparative Example 4, there are fewer hindered amine light stabilizers, and the free radicals generated after ultraviolet irradiation cannot be fully captured, the degradation rate of the material is accelerated, the surface and internal structure of the material are easily damaged, and the mechanical properties are all decreased.

[0067] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a composite material for improving the UV resistance of HDPE, characterized in that the preparation method comprises: Step S1, placing HDPE particles in a vacuum drying oven and drying them at a first temperature; Dissolving the hindered amine light stabilizer in a reaction solvent to prepare a mixed solution A, mixing the dried HDPE with the mixed solution A, adding an initiator, setting a reflux condenser, heating to a second temperature under the protection of an inert gas for reaction, cooling to room temperature after the reaction is completed, washing the product with a reaction solvent, placing the washed product in a vacuum dryer, and drying at a third temperature to obtain a product A; Step S2, adding a silane coupling agent to a reaction solvent, adding a catalyst, and then adding deionized water for hydrolysis reaction, and stirring under the protection of an inert gas to obtain a mixed solution B, mixing the product A with the mixed solution B, reacting at a fourth temperature under the protection of an inert gas, cooling to room temperature after the reaction is completed, and washing the product with a reaction solvent, placing the washed product in a vacuum dryer, and drying at a third temperature to obtain a product B; Step S3, adding product B at the second temperature, and adding elastomer, plasticizer, lubricant and antioxidant in sequence after product B is melted, mixing evenly and cooling and granulating to obtain a composite material with improved anti-UV performance of HDPE.

2. The method for preparing a composite material for improving the UV resistance of HDPE according to claim 1, characterized in that: In step S1, The mass of the HDPE is 20-30g; The first temperature is 60-70°C; The drying time at the first temperature is 4-6 hours; The hindered amine light stabilizer is Tinuvin 770; The reaction solvent is dichloromethane, and the volume is 100 mL.

3. The method for preparing a composite material for improving the UV resistance of HDPE according to claim 1, characterized in that: In step S1, The mass fraction of the mixed solution A is 0.5-2.0wt.%; The initiator is potassium persulfate, the mass of which is 0.5-1% of the mass of HDPE; The inert gas is nitrogen; The gas flow rate is 4-6 mL / min.

4. The method for preparing a composite material for improving the UV resistance of HDPE according to claim 1, characterized in that: In step S1, The second temperature is 180-200°C; The reaction time is 2-3h; The third temperature is 55-65°C; The drying time at the third temperature is 6-8 hours.

5. The method for preparing a composite material for improving the UV resistance of HDPE according to claim 1, characterized in that: In step S2, The silane coupling agent is vinyl triethoxysilane, and its mass is 1-2% of the mass of the product A; The reaction solvent is dichloromethane, with a volume of 150-200 mL; The catalyst is dibutyltin dilaurate, and its mass is 0.05-0.2% of the mass of the product A.

6. The method for preparing a composite material for improving the UV resistance of HDPE according to claim 1, characterized in that: In step S2, The mass of the deionized water is 2-5g; The inert gas is nitrogen; The gas flow rate is 4-6 mL / min.

7. The method for preparing a composite material for improving the UV resistance of HDPE according to claim 1, characterized in that: In step S2, The mass of the product A is 20-30g; The fourth temperature is 150-180°C; The inert gas is nitrogen; The gas flow rate is 4-6 mL / min; The reaction time is 1-2h.

8. The method for preparing a composite material for improving the UV resistance of HDPE according to claim 1, characterized in that: In step S2, The third temperature is 55-65°C; The drying time is 6-8h.

9. The method for preparing a composite material for improving the UV resistance of HDPE according to claim 1, characterized in that: In step S3, The second temperature is 180-200°C; The mass of the product B is 30-40g; The elastomer is ethylene octene copolymer or ethylene-vinyl acetate copolymer, with a mass of 3-5g; The plasticizer is tributyl citrate or di(2-ethylhexyl) phthalate, with a mass of 1-2 g; The lubricant is zinc stearate, with a mass of 1-2g; The antioxidant is antioxidant 1010 or antioxidant 168, with a mass of 2-3 g.

10. A composite material for improving the UV resistance of HDPE, prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Anti-ultraviolet polyethylene material for plastic road barrier

    CN108864528A

  • Polypropylene material and preparation method thereof

    CN102827421A

  • Automobile air pipe material and preparation method thereof

    CN105733074A

  • Reactive type light stabilizer and preparation method thereof

    CN107022111A

  • Alkoxy-modified low-alkali hindered amine light stabilizer as well as preparation and application thereof

    CN111285795A